PENGEMBANGAN KAWASAN PEDESAAN MELALUI INTRODUKSI TEKNOLOGI BIOGAS SNI 7826: 2012 DI DIY SEBAGAI MODEL INDUSTRI KREATIF BERBASIS SYARIAH - Meidi Syaflan; Ngatirah Ngatirah; Sunardi Sunardi; Nadime Lasykar Muhammad (Asian Journal of Innovation and Entrepreneurship, 2015)
ABSTRACTEfforts to change the face of rural areas into areas of economic development of creative industry by introducing energy-producing biogas as a clean, cheap and sustainable DIY in several villages in the region have shown initial results were quite encouraging. The successful development of domestic supply biogas owner of the house (blue) is an abundance of energy in the form of biogas (methane) and Bio-slurry that can be used to support agriculture in the broad sense. Nevertheless there are still many obstacles faced to optimize resource potential of the rural economy to become a regional economic development of the creative industry, especially with regard to government policies and regulations are likely to turn off social capital that is rooted in the community. To eliminate that in addition to the new approach in the implementation of rural development by the government also considered necessary to foster strong institutions and deeply rooted in the community for such activities umbrella, sharia-based economic organization like BMT may be an option for this purpose. Keywords: Biogas; bio-slurry; social capital and BMT